COVID‐19: A trigger of autoimmune diseases. (5th February 2023) - Zebardast, Arghavan; Hasanzadeh, Ali; Ebrahimian Shiadeh, Seyedeh Arefeh; Tourani, Mehdi; Yahyapour, Yousef
Abstract: The SARS‐coronavirus‐2 (SARS‐CoV‐2) that causes coronavirus disease 2019 (COVID‐19), has spread worldwide and caused a global health emergency. SARS‐CoV‐2 is a coronaviridae virus that infects target cells by interacting with the plasma membrane‐expressed angiotensin‐converting enzyme 2 (ACE2) via the S1 component of the S protein. Effective host immune response to SARS‐CoV‐2 infection, which includes both innate and adaptive immunity, is critical for virus management and elimination. The intensity and outcome of COVID‐19 may be related to an overabundance of pro‐inflammatory cytokines, which results in a "cytokine storm" and acute respiratory distress syndrome. After SARS‐CoV‐2 infection, the immune system's hyperactivity and production of autoantibodies may result in autoimmune diseases such as autoimmune hemolytic anemia, autoimmune thrombocytopenia, Guillain‐Barré syndrome, vasculitis, multiple sclerosis, pro‐thrombotic state, and diffuse coagulopathy, as well as certain autoinflammatory conditions such as Kawasaki disease in children. We have reviewed the association between COVID‐19 and autoimmune disorders in this article.